Cold sensitivity among female clinical nurses in Japan: A nationwide study - Miyuki Suzuki; Toshie Tsuchida; Aki Ibe (International Journal of Nursing Studies Advances, 2024)
Objectives: This study aimed to clarify the nature of cold sensitivity in female nurses working in hospitals in Japan. Design: A cross-sectional post survey research design. Settings: The questionnaire targeted nurses working in 14 hospitals across ten prefectures throughout Japan. Participants: 1,138 female nurses Methods: The survey captured participants’ characteristics, work environment, health, and lifestyle. The factors investigated were perceived cold sensitivity, cold sensitivity according to the Hiesho Sensation Scale, and cold sensitivity during nursing care. The Diagnostic Inventory of Health and Life Habits (DIHAL.2) assessed health and lifestyle habits. Results: Of the respondents, 44.3 % were aware of daily cold sensitivity and 21.4 % had a cold sensitivity disorder. The majority of respondents (63.1 %) felt cold in their hands when providing nursing care, and 28.1 % felt discomfort due to the coldness of their hands. Individuals diagnosed with cold sensitivity disorders exhibited poorer overall health compared to those without such disorders. However, there was no statistically significant difference in the overall health status between individuals who reported perceiving cold sensitivity and those who did not. The group with perceived cold sensitivity had significantly lower scores on exercise behavior, meal regularity, rest, sleep regularity, and sleep sufficiency. The proportion of female nurses working in Japanese hospitals who experienced cold sensitivity was similar to that of Japanese women with the same sensitivity. Most female nurses experienced cold in their hands while providing care. Nearly 30 % of the respondents experienced discomfort owing to cold hands. Conclusions: The study underscores the widespread issue of cold sensitivity among female nurses in Japanese hospitals, emphasizing the critical need for targeted interventions to improve their comfort and optimize care provision.